Non-aqueous electrolyte secondary battery
The integration of a sulfur-mesoporous carbon complex in the positive electrode and a fluorinated solvent in the nonaqueous electrolyte of nonaqueous electrolyte secondary batteries enhances capacity retention by mitigating lithium polysulfide elution, thereby addressing the capacity degradation issue in sulfur-based batteries.
Patent Information
- Application Number
- JP2020554043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-12
- Filing Date
- 2019-10-31
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2039-10-31
AI Technical Summary
Existing nonaqueous electrolyte secondary batteries using sulfur as the positive electrode material suffer from capacity degradation due to the solubility of lithium polysulfides in the electrolyte, leading to sulfur elution and reduced performance upon repeated charge and discharge.
A nonaqueous electrolyte secondary battery design featuring a positive electrode composed of a sulfur-mesoporous carbon complex, combined with a nonaqueous electrolyte containing a fluorinated solvent such as a chain fluorinated carbonate or carboxylic acid ester, which helps in suppressing the elution of lithium polysulfides and enhancing capacity retention.
The proposed battery configuration significantly improves the capacity retention rate of sulfur-based batteries during repeated charge and discharge cycles, effectively addressing the issue of capacity degradation.
Smart Images

Figure 0007655726000012 
Figure 0007655726000013 
Figure 0007655726000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] BACKGROUND ART Non-aqueous electrolyte secondary batteries, typified by lithium ion secondary batteries, have high energy density and high power density, and are therefore widely used in electronic devices such as personal computers and communication terminals, automobiles, and the like.
[0003] As positive electrode materials for lithium-ion secondary batteries, LiCoO2, LiNiO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Although lithium transition metal composite oxides such as O2 have been put to practical use, these materials have limited capacity per mass. Therefore, in order to realize non-aqueous electrolyte secondary batteries with higher energy density, sulfur is being considered as a positive electrode material to replace lithium transition metal composite oxides. Sulfur has a theoretical capacity per mass of 1675 mAhg. -1 This has an energy density that is more than six times the theoretical capacity of conventional positive electrode materials.
[0004] However, in non-aqueous electrolyte secondary batteries that use sulfur as the positive electrode active material, lithium polysulfide (Li2S) of some compositions is an intermediate product that is generated during charging and discharging. x Since (4≦x≦8) is soluble in the non-aqueous electrolyte, repeated charge and discharge causes sulfur to dissolve into the non-aqueous electrolyte as lithium polysulfide, resulting in a problem of reduced capacity.
[0005] In response to this, a technique has been proposed for improving the capacity decrease by adjusting the components of the non-aqueous electrolyte.
[0006] Non-Patent Document 1 describes a lithium ion secondary battery containing sulfur as a positive electrode active material, in which 1 moldm -3It is disclosed that LiTFSI (Lithium bis(trifluoromethanesulfonyl)imide) / FEC (fluoroethylene carbonate): D2 (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) is used.
[0007] Patent Document 1 discloses a nonaqueous electrolyte secondary battery that uses a positive electrode containing a carbon composite material containing sulfur and a carbon material having a pore volume ratio (micropores / mesopores) of 2.1, and a nonaqueous electrolyte obtained by mixing HF2CCF2CH2OCF2CF2H and FEC in a nonaqueous electrolyte solution at a ratio of 60:40, and adding LiTFSI to the nonaqueous electrolyte solution at a concentration of 1.0 mol / L. [Prior art documents] [Non-patent literature]
[0008] [Non-Patent Document 1] 58th Battery Symposium Abstracts, 1E16(2017) [Patent Document 1] International Publication No. WO2018 / 163778 Summary of the Invention [Problem to be solved by the invention]
[0009] Neither the secondary battery disclosed in Non-Patent Document 1 nor the secondary battery disclosed in Patent Document 1 was able to sufficiently suppress the decrease in capacity due to repeated charge and discharge. Therefore, there has been a demand for a non-aqueous electrolyte secondary battery containing a sulfur-based active material that can retain capacity even after repeated charge and discharge.
[0010] An object of the present invention is to provide a non-aqueous electrolyte secondary battery having a positive electrode containing a sulfur-based active material that has a high capacity retention rate during repeated charge and discharge. [Means for solving the problem]
[0011] One aspect of the present invention made to achieve the above object is a nonaqueous electrolyte secondary battery including a positive electrode and a nonaqueous electrolyte, wherein the positive electrode contains a sulfur-mesoporous carbon composite obtained by combining a sulfur-based active material with mesoporous carbon, and the nonaqueous electrolyte contains a fluorinated solvent, and the fluorinated solvent contains a chain fluorinated carbonate, a chain fluorinated carboxylic acid ester, or a combination thereof. [Effects of the Invention]
[0012] According to the present invention, it is possible to provide a nonaqueous electrolyte secondary battery having a positive electrode containing a sulfur-based active material that exhibits a high capacity retention rate during repeated charge and discharge. [Brief explanation of the drawings]
[0013] [Figure 1] FIG. 1 is an external perspective view showing one embodiment of a nonaqueous electrolyte secondary battery. [Figure 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device configured by assembling a plurality of nonaqueous electrolyte secondary batteries. DETAILED DESCRIPTION OF THE INVENTION
[0014] First, an outline of the nonaqueous electrolyte secondary battery disclosed in this specification will be described.
[0015] A nonaqueous electrolyte battery according to one embodiment of the present invention is a nonaqueous electrolyte secondary battery including a positive electrode and a nonaqueous electrolyte, wherein the positive electrode contains a sulfur-mesoporous carbon composite obtained by combining a sulfur-based active material with mesoporous carbon, and the nonaqueous electrolyte contains a fluorinated solvent, and the fluorinated solvent contains a chain fluorinated carbonate, a chain fluorinated carboxylic acid ester, or a combination thereof.
[0016] This configuration can increase the capacity retention rate when charging and discharging are repeated.
[0017] The reason for this is not clear, but the following is speculated, for example. Chain fluorinated carbonates and chain fluorinated carboxylic acid esters are less susceptible to reductive decomposition than fluorinated ethers, etc. Therefore, it is believed that in the nonaqueous electrolyte secondary battery, decomposition of the fluorinated solvent in the negative electrode can be suppressed. Furthermore, chain fluorinated carbonates and chain fluorinated carboxylic acid esters are more susceptible to oxidative decomposition than fluorinated ethers, etc. Therefore, it is believed that a coating is more likely to be formed at the interface between the sulfur-based active material and the non-aqueous electrolyte, thereby suppressing the elution of lithium polysulfides. Furthermore, mesoporous carbon has larger pore diameters than microporous carbon, which is thought to increase the contact area between the coating formed on the surface of the sulfur-based active material and the nonaqueous electrolyte, thereby facilitating the transport of carrier ions through the coating. It is believed that this phenomenon brings about a synergistic effect, which can increase the capacity retention rate when repeatedly charged and discharged.
[0018] Here, the total content of the chain fluorinated carbonate and the chain fluorinated carboxylic acid ester in the nonaqueous electrolyte solution may be 20% by volume or more.
[0019] This configuration makes it possible to more reliably achieve the effect of the present invention of increasing the capacity retention rate when charging and discharging are repeated.
[0020] Here, the fluorinated solvent may contain a cyclic fluorinated carbonate.
[0021] This configuration can improve the output characteristics of the nonaqueous electrolyte secondary battery.
[0022] Here, the non-aqueous electrolyte may contain a non-fluorinated solvent.
[0023] This configuration can increase the capacity retention rate when charging and discharging are repeated.
[0024] The reason for this is not clear, but the following is speculated, for example. The non-fluorinated solvent reacts more easily with lithium polysulfide than chain fluorinated carbonates and chain fluorinated carboxylic acid esters, which is thought to facilitate the formation of a coating on the surface of the sulfur-based active material, thereby suppressing the elution of lithium polysulfide and achieving the above-mentioned effect.
[0025] Here, the content of the non-fluorinated solvent in the non-aqueous electrolyte may be 1% by volume or more and 40% by volume or less.
[0026] This configuration can increase the capacity retention rate when charging and discharging are repeated.
[0027] Here, the non-fluorinated solvent may include a non-fluorinated organic compound containing a C═O double bond in the molecular structure.
[0028] This configuration can increase the capacity retention rate when charging and discharging are repeated.
[0029] The reason for this is not clear, but the following is speculated, for example. Non-fluorinated organic compounds containing C=O double bonds are particularly reactive with lithium polysulfides. It is believed that using a non-aqueous electrolyte containing such non-fluorinated organic compounds ensures the formation of a coating on the surface of the sulfur-based active material. As a result, sulfur elution is suppressed, and the discharge capacity retention rate during repeated charge and discharge is increased.
[0030] Here, the content of the chain fluorinated ether in the fluorinated solvent may be 0% by volume or more and 15% by volume or less.
[0031] This ensures that the effect of increasing the capacity retention rate when charging and discharging are repeated can be achieved.
[0032] Here, the fluorinated solvent may contain a chain fluorinated ether, and the content of the chain fluorinated ether in the fluorinated solvent may be 5% by volume or more and 15% by volume or less.
[0033] This configuration makes it possible to increase the capacity retention rate during repeated charge and discharge, while also increasing the discharge capacity at the beginning of the charge and discharge cycle.
[0034] The reason for this is not clear, but the following is speculated, for example. Chain fluorinated ethers have higher oxidation resistance and lower reduction resistance than chain fluorinated carbonates and chain fluorinated carboxylic acid esters. Therefore, it is believed that by including 5% to 15% by volume of a chain fluorinated ether in a nonaqueous electrolyte, the reactivity of the fluorinated solvent at the positive electrode can be appropriately reduced and oxidative decomposition of the fluorinated solvent can be suppressed without significantly impairing reduction resistance. This mechanism is believed to increase the capacity retention rate during repeated charge and discharge, while also increasing the discharge capacity at the early stage of the charge and discharge cycle.
[0035] The configuration and manufacturing method of a nonaqueous electrolyte secondary battery (hereinafter simply referred to as a "battery") according to one embodiment of the present invention will be described in detail below, taking a lithium secondary battery (hereinafter simply referred to as a "lithium battery") as an example. Note that the names of the components used in each embodiment may differ from the names of the components used in the background art.
[0036] <Nonaqueous electrolyte secondary battery> A battery according to one embodiment of the present invention includes a positive electrode, a negative electrode, and a non-aqueous electrolyte solution.
[0037] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode mixture layer disposed on the positive electrode substrate directly or via an intermediate layer.
[0038] The positive electrode substrate is conductive. Examples of the material for the positive electrode substrate include metals such as aluminum, titanium, tantalum, and stainless steel, as well as alloys thereof. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. Examples of the positive electrode substrate include foils and vapor-deposited films, with foils being preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085P and A3003P as specified in JIS-H-4000 (2014).
[0039] The lower limit of the average thickness of the positive electrode substrate is preferably 5 μm, more preferably 10 μm. The upper limit of the average thickness of the positive electrode substrate is preferably 50 μm, more preferably 40 μm. When the average thickness of the positive electrode substrate is equal to or greater than the above lower limit, the strength of the positive electrode substrate can be increased. When the average thickness of the positive electrode substrate is equal to or less than the above upper limit, the energy density per volume of the battery can be increased. "Average thickness" refers to the average value of thicknesses measured at any ten points. The same definition is used when "average thickness" is used for other components, etc.
[0040] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode mixture layer. The intermediate layer contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode mixture layer. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles. "Conductive" refers to a layer having a volume resistivity of 10 as measured in accordance with JIS-H-0505 (1975). 7 "Non-conductive" means that the volume resistivity is 10 Ω·cm or less. 7 This means that the resistance is greater than Ω·cm.
[0041] The positive electrode mixture layer contains a positive electrode active material and, if necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.
[0042] The positive electrode of the present invention includes a sulfur-mesoporous carbon composite in which a sulfur-based active material and mesoporous carbon are combined. The term "composite" used here refers to immobilizing the sulfur-based active material on the surface of the conductive material to such an extent that the sulfur-based active material does not separate from the conductive material.
[0043] Examples of sulfur-based active materials include elemental sulfur, metal sulfides, and organic sulfur compounds. Examples of metal sulfides include Li2S x (1≦x≦8), MS x (M=Ni, Co, Cu, Fe, Mo, Ti, 1≦x≦4) and the like. The organic sulfur compound may be an organic disulfide compound.
[0044] As used herein, mesoporous carbon refers to porous carbon in which the mesopore volume is greater than the micropore volume. Mesopore volume and micropore volume are calculated by the gas adsorption method. Specifically, the procedure is as follows: A porous carbon sample is dried overnight at 120°C. Then, the nitrogen gas adsorption / desorption isotherm of this sample at 77K is measured. From the desorption side isotherm of the measured adsorption / desorption isotherm, the pore distribution is calculated using the BJH method and the MP method. The pore volume derived from pores with a diameter of 2 nm to 50 nm, obtained from the calculation results using the BJH method, is taken as the mesopore volume. The pore volume derived from pores with a diameter of less than 2 nm, obtained from the calculation results using the MP method, is taken as the micropore volume. When a porous carbon sample is to be collected from the positive electrode taken out by disassembling a non-aqueous electrolyte secondary battery, the following procedure is used for preparation. First, the non-aqueous electrolyte secondary battery is charged at a constant current of 0.05 C. The constant current charging is performed when the potential of the positive electrode is 3 V (vs. Li / Li +) until the voltage reaches a constant value. Next, the battery is charged at a constant voltage until the current value decreases to 0.02 C. The nonaqueous electrolyte secondary battery is then disassembled and the positive electrode is removed. The removed positive electrode is washed with DMC (dimethyl carbonate) and dried at room temperature for one day and one night, after which the positive electrode mixture is recovered. This positive electrode mixture is then washed with water to extract the sulfur-porous carbon composite. This sulfur-porous carbon is then heat-treated at 200°C to obtain a porous carbon sample for measurement.
[0045] The content of the sulfur-based active material in the sulfur-mesoporous carbon composite is preferably 50% by mass to 95% by mass, which can increase the energy density and electronic conductivity of the sulfur-mesoporous carbon composite.
[0046] The total pore volume per unit mass of the mesoporous carbon is preferably 1 to 2 times the volume density of the sulfur-based active material in a discharged state. For example, if the volume density of the sulfur-based active material in a charged state is 0.9 cm 3 g -1 When elemental sulfur is used and the content of elemental sulfur in the sulfur-mesoporous carbon composite is 50 mass%, the total pore volume per unit mass is 0.9 cm 3 g -1 Over 1.8cm 3 g -1 This makes it possible to increase the energy density of the sulfur-mesoporous carbon composite while retaining sufficient sulfur within the pores.
[0047] The mesopore volume per unit mass of mesoporous carbon is 0.50 cm 3 g -1 More than 2.0cm 3 g -1 Preferably, it is less than 0.60 cm. 3 g -1 Over 1.8cm 3 g -1 It is more preferable that it is 0.70 cm or less. 3 g -1 More than 1.5cm 3 g -1This makes it possible to increase the energy density of the sulfur-mesoporous carbon composite while suppressing a decrease in the bulk density of the positive electrode mixture.
[0048] The micropore volume per unit mass of mesoporous carbon is 0.18 cm 3 g -1 More than 0.50cm 3 g -1 Preferably, it is less than 0.24 cm. 3 g -1 Over 0.44cm 3 g -1 It is more preferable that it is 0.30 cm or less. 3 g -1 More than 0.38cm 3 g -1 This makes it possible to increase the energy density of the sulfur-mesoporous carbon composite while suppressing a decrease in the bulk density of the positive electrode mixture.
[0049] The ratio of the mesopore volume to the micropore volume of the mesoporous carbon may have a lower limit of 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. This increases the contact area between the coating formed on the surface of the sulfur-based active material in the sulfur-mesoporous carbon composite and the nonaqueous electrolyte. The upper limit of the ratio of the mesopore volume to the micropore volume is not particularly limited, but may be, for example, 10 or less. This increases the electronic conductivity of the sulfur-based active material in the sulfur-mesoporous carbon composite.
[0050] The mesoporous carbon preferably has a peak in the range of 1.0 nm to 6.0 nm in the log differential pore volume distribution, which increases the permeability of the electrolyte into the pores while reducing the size of the sulfur-based active material particles supported in the pores.
[0051] It is preferable that the mesoporous carbon has a single peak in the log differential pore volume distribution, which makes the particle diameter of the sulfur-based active material particles in the sulfur-mesoporous carbon composite uniform and increases the utilization rate of the sulfur-based active material.
[0052] The mesoporous carbon preferably has a half-width of 1.0 nm to 2.5 nm in the log differential pore volume distribution, which makes the particle diameter of the sulfur-based active material particles in the sulfur-mesoporous carbon composite uniform and increases the utilization rate of the sulfur-based active material.
[0053] The average pore diameter of the mesoporous carbon is preferably 0.5 nm to 15 nm, more preferably 0.7 nm to 10 nm, and even more preferably 1.0 nm to 6.0 nm. The average pore diameter here refers to the value obtained by dividing the total pore volume calculated by the BJH method by the BET specific surface area. By setting the average pore diameter to be equal to or larger than these lower limits, the size of the sulfur-based active material particles contained in the sulfur-mesoporous carbon composite can be reduced, thereby improving ionic conductivity and electronic conductivity.By setting the average pore diameter to be equal to or smaller than these upper limits, the permeability of the nonaqueous electrolyte into the pores of the sulfur-mesoporous carbon composite can be improved.
[0054] The BET specific surface area of mesoporous carbon is 1000m 2 g -1 Over 4000m 2 g -1 It is preferable that it is less than 1500m 2 g -1 More than 3500m 2 g -1 It is more preferable that it is less than 2000m 2 g -1 More than 3000m 2 g -1It is more preferable that the total surface area of the sulfur-based active material and the mesoporous carbon be equal to or less than 1000 nm. This increases the contact area between the sulfur-based active material and the mesoporous carbon. It also increases the contact area between the sulfur-based active material contained in the sulfur-mesoporous carbon composite and the nonaqueous electrolyte.
[0055] The mesoporous carbon is not particularly limited in shape or size as long as it is a porous carbon in which the mesopore volume is larger than the micropore volume.
[0056] In addition, the positive electrode according to one embodiment of the present invention may contain an active material other than the sulfur-based active material in addition to the sulfur-based active material. Such an active material can be appropriately selected from known positive electrode active materials. Specific examples include lithium-transition metal composite oxides, transition metal oxides, and polyanion compounds.
[0057] (optional ingredient) The positive electrode mixture layer may contain a conductive agent. By containing a conductive agent, the electronic conductivity of the positive electrode mixture layer can be increased. The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include graphite; carbon black such as furnace black and acetylene black; metals; and conductive ceramics. The conductive agent may be in the form of powder or fiber. Among these, acetylene black is preferred from the viewpoints of electronic conductivity and coatability.
[0058] The lower limit of the content of the conductive agent in the positive electrode mixture layer is preferably 1 mass %, more preferably 3 mass %. The upper limit of the content of the conductive agent is preferably 15 mass %, more preferably 10 mass %. By setting the content of the conductive agent within the above range, the electrical capacity of the battery can be increased.
[0059] When a sulfur-porous carbon composite is used, the porous carbon also functions as a conductive agent. Therefore, by using the sulfur-porous carbon composite, it is expected that good electronic conductivity can be exhibited even when the positive electrode mixture layer does not contain the conductive agent. The sulfur-porous carbon composite and the conductive agent may be used in combination.
[0060] When porous carbon and a conductive agent are used in combination, the upper limit of the total content of porous carbon and conductive agent in the positive electrode mixture layer is preferably 40 mass %, more preferably 30 mass %.
[0061] The binder used in the positive electrode mixture layer is usually one that can fix the positive electrode active material and is electrochemically stable within the range of use. Either an aqueous binder or a non-aqueous binder may be used as the binder.
[0062] A water-based binder is a binder that disperses or dissolves in water. Among them, a binder that dissolves at least 1 part by mass in 100 parts by mass of water at 20°C is preferred as the water-based binder. Examples of water-based binders include polyethylene oxide (polyethylene glycol), polypropylene oxide (polypropylene glycol), polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyethylene (PE), polypropylene (PP), polyethyleneimine (PEI), nitrile-butadiene rubber, and cellulose.
[0063] The non-aqueous binder is a binder that disperses or dissolves in a non-aqueous solvent such as N-methylpyrrolidone (NMP). Among them, a binder that dissolves at 1 part by mass or more per 100 parts by mass of NMP at 20°C is preferred as the non-aqueous binder. Examples of non-aqueous binders include polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and hexafluoropropylene (PVDF-HFP), a copolymer of ethylene and vinyl alcohol, polyacrylonitrile, polyphosphazene, polysiloxane, polyvinyl acetate, polymethyl methacrylate (PMMA), polystyrene, polycarbonate, polyamide, polyimide, polyamideimide, a crosslinked polymer of cellulose and chitosan pyrrolidone carboxylate, and chitin or chitosan derivatives.
[0064] When a binder is used, if the binder is aqueous, a paste is formed using water as the dispersion medium, and if the binder is non-aqueous, a paste is formed using a non-aqueous solvent as the dispersion medium. The formed paste is applied to a positive electrode substrate and dried to form a positive electrode mixture layer. Here, since the temperature at which sulfur sublimes is about 180°C, it is preferable to use a solvent with a boiling point lower than 180°C as the dispersion medium for the paste. As a solvent with a boiling point lower than 180°C, it is particularly preferable to use water, which has a low melting point and is easy to handle. For these reasons, it is preferable to use an aqueous binder as the binder.
[0065] The lower limit of the binder content in the positive electrode mixture layer is preferably 1 mass %, more preferably 3 mass %. The upper limit of the binder content is preferably 15 mass %, more preferably 10 mass %. By setting the binder content within the above range, the active material can be stably fixed.
[0066] Examples of thickeners include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0067] The filler is not particularly limited, and examples of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and alumina silicate.
[0068] The positive electrode mixture layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, and I; typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0069] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode mixture layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode above.
[0070] The negative electrode substrate is conductive. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, are used as the material for the negative electrode substrate. Among these, copper or a copper alloy is preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, with foils being preferred from the viewpoint of cost. Therefore, copper foil or a copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0071] The lower limit of the average thickness of the negative electrode substrate is preferably 3 μm, more preferably 5 μm. The upper limit of the average thickness of the negative electrode substrate is preferably 30 μm, more preferably 20 μm. By making the average thickness of the negative electrode substrate equal to or greater than the lower limit, the strength of the negative electrode substrate can be increased. By making the average thickness of the negative electrode substrate equal to or less than the upper limit, the energy density per volume of the battery can be increased.
[0072] The negative electrode mixture layer contains a negative electrode active material. The negative electrode mixture layer contains optional components such as a conductive agent, a binder (binding agent), a thickener, and a filler, as needed. The optional components such as the conductive agent, the binder, the thickener, and the filler can be selected from the materials exemplified for the positive electrode above.
[0073] The negative electrode mixture layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, and I; typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge; and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0074] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium secondary batteries. Examples of the negative electrode active material include metallic Li; metals or semimetals such as Si, Sn, and Sb; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; polyphosphate compounds; silicon carbide; and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon).
[0075] Among these materials, materials with low operating potential are preferred. Metallic Li is particularly preferred. In this embodiment, when a material not containing Li, such as graphite, is used as the negative electrode active material, a step of inserting lithium ions into either the positive electrode or the negative electrode is required. In contrast, metallic Li is preferred because the step of inserting lithium ions can be omitted if metallic Li is used as the negative electrode active material. In the negative electrode mixture layer, one of these materials may be used alone, or two or more may be used in combination.
[0076] Note that "graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of being able to obtain a material with stable physical properties.
[0077] "Non-graphitic carbon" refers to the carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. The crystallite size Lc of non-graphitic carbon is usually 0.80 to 2.0 nm. Examples of non-graphitic carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitic carbon include resin-derived materials, petroleum pitch-derived materials, and alcohol-derived materials.
[0078] Here, the "discharged state" refers to a state in which an open circuit voltage is 0.7 V or higher in a single-electrode battery using a negative electrode containing a carbon material as the negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the redox potential of Li. In other words, an open circuit voltage of 0.7 V or higher in the single-electrode battery means that lithium ions capable of being absorbed and released during charging and discharging have been sufficiently released from the carbon material, which is the negative electrode active material.
[0079] "Non-graphitizable carbon" means the above d 002 The term "non-graphitizable carbon" refers to a carbon material with a particle size of 0.36 nm or more and 0.42 nm or less. Non-graphitizable carbon is generally a type of non-graphitizable carbon that is difficult to form into a graphite structure with three-dimensional stacking regularity.
[0080] "Graphitizable carbon" means the above d 002 Graphitizable carbon is a carbon material with a particle size of 0.34 nm or more and less than 0.36 nm. Graphitizable carbon is typically a non-graphitic carbon that has the property of easily forming a graphite structure with three-dimensional stacking regularity.
[0081] The lower limit of the content of the negative electrode active material in the negative electrode mixture layer is preferably 60% by mass, more preferably 80% by mass, and even more preferably 90% by mass. By making the content of the negative electrode active material equal to or greater than the lower limit, the electrical capacity of the battery can be increased. The upper limit of the content of the negative electrode active material is preferably 99% by mass, and more preferably 98% by mass. By making the content of the negative electrode active material particles equal to or less than the upper limit, the production of the negative electrode becomes easier.
[0082] (separator) The separator can be appropriately selected from known separators. Examples of separators that can be used include separators consisting of only a substrate layer and separators in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer. Examples of materials for the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these materials, porous resin film is preferred from the viewpoint of strength, and nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. Materials for the substrate layer of the separator are preferably polyolefins such as polyethylene and polypropylene from the viewpoint of shutdown function, and polyimide and aramid from the viewpoint of oxidative decomposition resistance. A composite material of these resins may also be used for the substrate layer of the separator.
[0083] The heat-resistant particles contained in the heat-resistant layer preferably exhibit a weight loss of 5% or less at 500°C in air, and more preferably a weight loss of 5% or less at 800°C in air. Examples of materials exhibiting a weight loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, and aluminum oxide-silicon oxide composite oxide; nitrides such as aluminum nitride and silicon nitride; sparingly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate; covalently bonded crystals such as silicon and diamond; and mineral-derived substances or artificial products such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica. These inorganic compounds may be used alone or in combination of two or more. Among these inorganic compounds, silicon oxide, aluminum oxide, and aluminum oxide-silicon oxide composite oxide are preferred.
[0084] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0085] The separator may be a polymer gel composed of a polymer and a non-aqueous electrolyte. Examples of polymers include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of a polymer gel has the effect of suppressing battery leakage. The separator may be a combination of the porous resin film or nonwoven fabric described above and a polymer gel.
[0086] (Non-aqueous electrolyte) The nonaqueous electrolyte solution includes a nonaqueous solvent containing a fluorinated solvent and an electrolyte salt dissolved in the nonaqueous solvent. The nonaqueous electrolyte solution includes, as the fluorinated solvent, a chain fluorinated carboxylic acid ester, a chain fluorinated carbonate, or a combination thereof.
[0087] The non-aqueous electrolyte solution contains, for example, a chain fluorinated carboxylic acid ester represented by formula (1). Formula (1) TIFF0007655726000001.tif3667
[0088] In formula (1), R1 is hydrogen or a monovalent organic group, and R2 is a monovalent organic group. Examples of the organic group represented by R1 and R2 include hydrocarbon groups such as alkyl groups, cycloalkyl groups, alkenyl groups, and aryl groups each having 1 to 10 carbon atoms, hydrocarbon groups in which some or all of the hydrogen atoms of these groups have been substituted with functional groups such as halogen atoms (chlorine, fluorine, bromine, and iodine atoms), oxyalkylene groups, sulfo groups, thiol groups, aldehyde groups, cyano groups, and amide groups, and groups in which these hydrocarbon groups are interrupted by -O-, -NH-, -N(CH3)-, -SO2-, -CO-, -COO-, etc.
[0089] At least one of R1 and R2 is a fluorinated hydrocarbon group in which at least one hydrogen atom is substituted with a fluorine atom. Of R1 and R2, only R1 may be a fluorinated hydrocarbon group, only R2 may be a fluorinated hydrocarbon group, or both may be fluorinated hydrocarbon groups.
[0090] Examples of this chain fluorinated carboxylic acid ester include methyl 2,2-difluoroacetate, methyl 2,2,2-trifluoroacetate, ethyl 2,2,2-trifluoroacetate, methyl 3,3,3-trifluoropropionate, ethyl 3,3,3-trifluoropropionate, trifluoromethyl acetate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, trifluoromethyl propionate, 2,2,2-trifluoroethyl propionate, and 2,2,2-trifluoroethyl 3,3,3-trifluoropropionate.
[0091] The non-aqueous electrolyte solution contains, for example, a chain fluorinated carbonate represented by formula (2). Formula (2) TIFF0007655726000002.tif3376
[0092] In formula (2), R3 and R4 are each independently a monovalent organic group. Examples of the organic groups represented by R3 and R4 include the same organic groups as those exemplified for R1 and R2.
[0093] At least one of R3 and R4 is a fluorinated hydrocarbon group in which at least one hydrogen atom is substituted with a fluorine atom. Of R3 and R4, only R3 may be a fluorinated hydrocarbon group, only R4 may be a fluorinated hydrocarbon group, or both may be fluorinated hydrocarbon groups.
[0094] Examples of this chain fluorinated carbonate include 2,2-difluoroethyl methyl carbonate, ethyl-(2,2-difluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, 2,2,2-trifluoroethyl methyl carbonate, ethyl-(2,2,2-trifluoroethyl) carbonate, and bis(2,2,2-trifluoroethyl) carbonate.
[0095] In the fluorinated hydrocarbon groups of formula (1) and formula (2), the number of fluorine atoms to be substituted is not particularly limited, as long as it is one or more. Furthermore, it is believed that a small number of fluorine atoms to be substituted reduces oxidation resistance and increases reduction resistance, making it easier to form a coating at the positive electrode and less susceptible to reductive decomposition at the negative electrode. From this perspective, the number of fluorine atoms to be substituted is preferably six or less, more preferably five or less, even more preferably four or less, and even more preferably three or less. The carbon to which the fluorine atom is bonded is not particularly limited, and may be a carbon located at the terminal of the hydrocarbon group or a carbon other than the terminal.
[0096] In formula (1) and formula (2), the hydrocarbon groups of R1, R2, R3, and R4 preferably have 1 to 8 carbon atoms, more preferably 1 to 5 carbon atoms, and even more preferably 1 to 3 carbon atoms. By adjusting the carbon number to these values, the viscosity of the chain fluorinated carboxylic acid ester or chain fluorinated carbonate can be reduced.
[0097] When R1, R2, R3, and R4 are organic groups other than fluorinated hydrocarbon groups, these organic groups are preferably alkyl or alkenyl groups, more preferably alkyl groups, and may be linear or branched.
[0098] Examples of the alkyl group include CH3-, CH3CH2-, CH3CH2CH2-, and the like, and examples of the alkenyl group include CH2=CH-, CH2=CHCH2-, CH2=C(CH3)-, and the like.
[0099] The lower limit of the total content of the chain fluorinated carboxylic acid ester and the chain fluorinated carbonate in the nonaqueous electrolyte is preferably 20% by volume or more, more preferably 30% by volume or more, even more preferably 40% by volume or more, and even more preferably 50% by volume or more. The upper limit is 100% by volume or less, and may be 90% by volume or less, 80% by volume or less, or 70% by volume or less. This more reliably achieves the effect of the present invention, which is to increase the capacity retention rate during repeated charge and discharge.
[0100] The reason for this is not clear, but the following is speculated, for example. It is believed that the chain-type fluorinated carboxylic acid ester and chain-type fluorinated carbonate contained in the non-aqueous electrolyte undergo oxidative decomposition at the positive electrode to form a coating on the surface of the sulfur-based positive electrode active material. This coating reduces the area of direct contact between the sulfur-based active material and the non-aqueous electrolyte, thereby suppressing the elution of lithium polysulfide into the non-aqueous electrolyte. However, because the volume of the sulfur-based active material changes significantly during charge and discharge, repeated charge and discharge may cause cracks in the coating, leading to the elution of lithium polysulfide into the non-aqueous electrolyte. When the total content of the chain fluorinated carboxylic acid ester and the chain fluorinated carbonate in the nonaqueous electrolyte is 20% by volume or more, a new coating is easily formed even if the coating cracks, which is believed to reliably suppress the elution of lithium polysulfide and increase the capacity retention rate during repeated charge and discharge.
[0101] The lower limit of the content of the chain fluorinated ether in the fluorinated solvent is 0% by volume, preferably more than 0% by volume, more preferably 5% by volume, and even more preferably 7% by volume. The upper limit of the content of the chain fluorinated ether in the fluorinated solvent is 20% by volume or less, preferably 18% by volume or less, more preferably 15% by volume or less, and even more preferably 10% by volume. By setting the content ratio of the chain fluorinated ether in the fluorinated solvent to the above value, it is possible to achieve both an increase in capacity retention during repeated charge and discharge and an increase in discharge capacity at the beginning of the charge and discharge cycle.
[0102] The reason for this is not clear, but the following is speculated, for example. Chain fluorinated ethers have higher oxidation resistance and lower reduction resistance than chain fluorinated carbonates and chain fluorinated carboxylic acid esters. Therefore, by including the chain fluorinated ether in the nonaqueous electrolyte solution in the above-mentioned content ratio, it is believed that the reactivity of the fluorinated solvent at the positive electrode can be appropriately reduced and the oxidative decomposition of the fluorinated solvent can be suppressed without significantly impairing the reduction resistance of the nonaqueous electrolyte solution. This mechanism is believed to increase the discharge capacity at the early stage of the charge-discharge cycle while increasing the capacity retention rate during repeated charge-discharge.
[0103] The chain fluorinated ether in the fluorinated solvent may include, for example, a chain fluorinated ether represented by formula (3). Formula (3) R5-O-R6
[0104] In formula (3), R5 and R6 are each independently a monovalent organic group. Examples of the organic groups represented by R5 and R6 include the same organic groups as those exemplified for R5 and R6.
[0105] At least one of R5 and R6 is a fluorinated hydrocarbon group in which at least one hydrogen atom is substituted with a fluorine atom. Of R5 and R6, only R5 may be a fluorinated hydrocarbon group, only R6 may be a fluorinated hydrocarbon group, or both may be fluorinated hydrocarbon groups.
[0106] Examples of this chain fluorinated ether include CF3CF2CH2OCH3, HCF2CF2OCH2CF2CF2H, HCF2CF2CH2OCF2CHFCF3, CF3CF2CH2OCF2CHFCF3, CF3CF2CH2OCF2CF2H, HCF2CF2OC2H5, HCF2CF2OC3H7, HCF2CF2OC4H9, CF3CHFCF2OC2H5, CF3CH2OCH2CH2OCH3, and the like.
[0107] In the fluorinated hydrocarbon group of formula (3), the number of substituted fluorine atoms may be 1 or more. There is no particular upper limit, but it may be, for example, 11 or less. There is no particular limit to the carbon to which the fluorine atom is bonded, and it may be a carbon located at the terminal of the hydrocarbon group or a carbon other than the terminal.
[0108] In formula (3), the hydrocarbon groups of R5 and R6 preferably have 1 to 8 carbon atoms, more preferably 1 to 5 carbon atoms, and even more preferably 1 to 4 carbon atoms. By adjusting the carbon number to these values, the viscosity of the chain fluorinated ether can be reduced.
[0109] When R5 and R6 are organic groups other than fluorinated hydrocarbon groups, these organic groups are preferably alkyl or alkenyl groups, more preferably alkyl groups, and may be linear or branched.
[0110] The nonaqueous electrolyte preferably contains a chain solvent and a cyclic solvent. The volume ratio of the chain solvent to the cyclic solvent in the nonaqueous electrolyte is preferably in the range of 30:70 to 70:30. This makes it possible to simultaneously reduce the viscosity of the nonaqueous electrolyte and increase the ionic conductivity of the nonaqueous electrolyte.
[0111] The lower limit of the content of the fluorinated solvent contained in the non-aqueous electrolyte may be 60 vol%, preferably 63 vol%, more preferably 65 vol%, even more preferably 68 vol%, and even more preferably 70 vol%, based on the total volume of the non-aqueous electrolyte. The upper limit of the content of the fluorinated solvent contained in the non-aqueous electrolyte is 100 vol%, may be 99 vol%, 98 vol%, 97 vol%, or may be 95 vol%, based on the total volume of the non-aqueous electrolyte. This can increase the capacity retention rate during repeated charge and discharge.
[0112] The fluorinated solvent preferably contains a chain fluorinated solvent and a cyclic fluorinated solvent. The volume ratio of the chain fluorinated solvent to the cyclic fluorinated solvent in the fluorinated solvent is preferably in the range of 30:70 to 70:30. This makes it possible to simultaneously reduce the viscosity of the nonaqueous electrolyte and increase the ionic conductivity of the nonaqueous electrolyte.
[0113] The content of the cyclic fluorinated solvent in the cyclic solvent contained in the non-aqueous electrolyte is preferably 50% by volume or more and 100% by volume or less, which can increase the capacity retention rate during repeated charge and discharge.
[0114] The fluorinated solvent preferably contains a cyclic fluorinated carbonate, which can promote dissociation of the electrolyte salt and increase the ionic conductivity of the non-aqueous electrolyte solution.
[0115] Examples of cyclic fluorinated carbonates include fluoroethylene carbonate (FEC), 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, trifluoropropylene carbonate (4-(trifluoromethyl)-ethylene carbonate), 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, etc. Among these, fluoroethylene carbonate, 4,4-difluoroethylene carbonate, and 4,5-difluoroethylene carbonate are preferred, and fluoroethylene carbonate is more preferred.
[0116] The non-aqueous electrolyte preferably contains a non-fluorinated solvent. By containing a non-fluorinated solvent in the non-aqueous electrolyte, the capacity retention rate can be further increased after repeated charge and discharge. Although the reason for this is unclear, it is speculated that the non-fluorinated solvent easily reacts with lithium polysulfide and easily forms a coating on the surface of the sulfur-based active material, which is the reason why the discharge capacity retention rate can be increased after repeated charge and discharge.
[0117] The non-fluorinated solvent is not particularly limited, but preferably includes a compound containing a C=O double bond in its molecular structure. Examples of such non-fluorinated solvents include carbonates, esters, aldehydes, and ketones. The use of such non-fluorinated solvents can increase the retention rate of discharge capacity during repeated charge and discharge.
[0118] The content of the compound containing a C═O double bond in the molecular structure of the non-fluorinated solvent is preferably 50% by volume to 100% by volume, more preferably 60% by volume to 100% by volume, even more preferably 70% by volume to 100% by volume, and even more preferably 80% by volume to 100% by volume, which can more reliably increase the retention rate of discharge capacity during repeated charge and discharge.
[0119] Carbonates that can be used as non-fluorinated solvents may be cyclic carbonates or chain carbonates. Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, catechol carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Among these, ethylene carbonate and propylene carbonate are preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, methyl-n-propyl carbonate, n-butyl methyl carbonate, isobutyl methyl carbonate, t-butyl methyl carbonate, ethyl-n-propyl carbonate, n-butyl ethyl carbonate, isobutyl ethyl carbonate, t-butyl ethyl carbonate, etc. Among these, dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate are preferred, and dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are particularly preferred.
[0120] Examples of esters that can be used as non-fluorinated solvents include cyclic carboxylic acid esters such as γ-butyrolactone and γ-valerolactone, and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.
[0121] The lower limit of the content of the non-fluorinated solvent contained in the non-aqueous electrolyte may be 1 vol%, preferably 2 vol%, more preferably 3 vol%, and even more preferably 5 vol%, based on the total volume of the non-aqueous electrolyte. The upper limit of the content of the non-fluorinated solvent contained in the non-aqueous electrolyte may be 40 vol%, preferably 35 vol%, more preferably 32 vol%, and even more preferably 30 vol%. This can increase the capacity retention rate during repeated charge and discharge.
[0122] The nonaqueous electrolyte may contain a known nonaqueous solvent in addition to the above. Examples of the nonaqueous solvent include carboxylic acid esters, phosphate esters, sulfonic acid esters, ethers, amides, and nitriles. Nonaqueous solvents in which some of the hydrogen atoms contained in these compounds have been substituted with halogens may also be used.
[0123] The electrolyte salt can be appropriately selected from known electrolyte salts, such as lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts. Of these, lithium salts are preferred.
[0124] Examples of lithium salts include inorganic lithium salts such as LiPF, LiPO, LiBF, LiClO, LiN(SOF), LiAsF, and lithium difluorooxalatoborate (LiFOB), and lithium salts having halogenated hydrocarbon groups such as LiSO, LiN(SOCF), LiN(SOCF), LiN(SOCF) and LiN(SOCF)(SOCF), LiC(SOCF) and LiC(SOCF). At least one selected from these may be used, or two or more may be used in combination. Among these, LiPF, LiBF, LiN(SOF), and LiN(SOCF) are preferred from the viewpoint of electrical conductivity, and LiN(SOF) and LiN(SOCF) are more preferred from the viewpoint of cation dissociation.
[0125] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte solution is preferably 0.1 M, more preferably 0.3 M, even more preferably 0.5 M, and particularly preferably 0.7 M. The upper limit of the content of the electrolyte salt is, for example, preferably 2.5 M, more preferably 2 M, and even more preferably 1.5 M.
[0126] The non-aqueous electrolyte may contain an additive. In this specification, the additive means an additive whose content in the non-aqueous electrolyte is less than 20 mass %. Examples of additives include salts having an oxalate ester group, such as lithium bis(oxalate)borate (LiBOB) and lithium bis(oxalate)difluorophosphate (LiFOP); aromatic compounds, such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds, such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds, such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexyl anisole. Examples of the additives include xanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, and lithium monofluorophosphate. These additives may be used alone or in combination of two or more.
[0127] The lower limit of the content of these additives relative to the total non-aqueous electrolyte solution is preferably 0.01% by mass, more preferably 0.1% by mass, and even more preferably 0.2% by mass. The upper limit of the content of the additives is preferably 10% by mass, more preferably 7% by mass, more preferably 5% by mass, and even more preferably 3% by mass. By setting the content of the additives within the above ranges, it is possible to improve capacity retention or charge / discharge cycle performance after high-temperature storage, and to improve safety.
[0128] The nonaqueous electrolyte secondary battery may include a solid electrolyte.
[0129] The solid electrolyte can be selected from any material that has ionic conductivity of lithium, sodium, calcium, etc., and is solid at room temperature (for example, 15° C. to 25° C.) Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, and polymer solid electrolytes.
[0130] In the case of a lithium secondary battery, examples of sulfide solid electrolytes include Li2S-P2S5 systems. Examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, and Li 10 Ge-P2S 12 , etc.
[0131] The shape of the nonaqueous electrolyte secondary battery is not particularly limited, and examples thereof include cylindrical batteries, pouch batteries, square batteries, flat batteries, coin batteries, and button batteries. An example of a prismatic battery is shown in Figure 1. An electrode assembly 2 having a positive electrode and a negative electrode wound with a separator sandwiched between them is housed in a prismatic case 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0132] <Configuration of the power storage device> The nonaqueous electrolyte secondary battery can be mounted as a power storage device comprising an energy storage unit (battery module) configured by assembling a plurality of nonaqueous electrolyte secondary batteries 1, and the energy storage device can be used as a power source for automobiles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), a power source for electronic devices such as personal computers and communication terminals, or a power storage power source. In this case, the technology of the present invention may be applied to at least one nonaqueous electrolyte secondary battery included in the energy storage device. 2 shows an example of a power storage device 30 in which power storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte secondary batteries 1, are further assembled. The power storage device 30 may include a bus bar (not shown) that electrically connects the two or more nonaqueous electrolyte secondary batteries 1, and a bus bar (not shown) that electrically connects the two or more power storage units 20. The power storage units 20 or the power storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more nonaqueous electrolyte secondary batteries.
[0133] <Manufacturing method of non-aqueous electrolyte secondary battery> The method for manufacturing the nonaqueous electrolyte secondary battery storage element can be appropriately selected from known methods. The manufacturing method includes, for example, the steps of preparing an electrode assembly, preparing a nonaqueous electrolyte, and housing the electrode assembly and the nonaqueous electrolyte in a container. The step of preparing the electrode assembly includes the steps of preparing a positive electrode and a negative electrode, and stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween to form the electrode assembly.
[0134] The step of placing the non-aqueous electrolyte in the container can be appropriately selected from known methods, for example, by injecting the non-aqueous electrolyte through an inlet formed in the container and then sealing the inlet.
[0135] <Other embodiments> The nonaqueous electrolyte secondary battery of the present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the spirit and scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, or part of the configuration of one embodiment may be replaced with the configuration of another embodiment or well-known technology. Furthermore, part of the configuration of one embodiment may be deleted. Furthermore, well-known technology may be added to the configuration of one embodiment.
[0136] In the above embodiment, the nonaqueous electrolyte secondary battery is described as being used as a lithium secondary battery, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte secondary battery are arbitrary. The present invention can also be applied to various nonaqueous electrolyte secondary batteries other than lithium secondary batteries. [Example]
[0137] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0138] [Example 1] (Preparation of sulfur-mesoporous carbon composites) Sulfur and mesoporous carbon (CNovel) (manufactured by Toyo Tanso Co., Ltd.) were mixed in a mass ratio of 77:23. The mesoporous carbon had an average pore diameter of 5 nm and a micropore volume of 0.34 ccg. -1 , mesopore volume 1.02cc -1 , total pore volume 1.7ccg -1 , specific surface area 1500m 2 g -1 This mixture was placed in a sealed electric furnace. After argon flow for 1 hour, the temperature was increased to 150°C at a rate of 5°C / min and maintained at that temperature for 5 hours. After that, the temperature was allowed to cool to 80°C, at which point sulfur solidifies. Thereafter, the temperature was increased again to 300°C at a rate of 5°C / min and maintained at that temperature for 2 hours. This heat treatment yielded the sulfur-mesoporous carbon composite of Example 1.
[0139] (Fabrication of non-aqueous electrolyte secondary battery) A sulfur-mesoporous carbon composite, acetylene black as a conductive additive, and CMC / SBR as a binder were mixed in a mass ratio of 80:10:10 to prepare a slurry using water as a dispersion medium. The CMC and SBR were mixed in a mass ratio of 1.2:2.1. The prepared slurry was applied to a current collector and dried to prepare an electrode. A battery was fabricated using the prepared electrode as the positive electrode, metallic Li as the negative electrode, and a nonaqueous electrolyte solution containing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) dissolved in a mixed solvent of 2,2,2-trifluoroethyl acetate (TFEA) and fluoroethylene carbonate (FEC). The TFEA / FEC mixture ratio was 50:50 by volume. The battery was then covered with an aluminum laminate film to form a pouch-type cell.
[0140] [Example 2] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of 2,2,2-trifluoroethyl methyl carbonate (TFEMC) and FEC was used as the solvent.
[0141] [Example 3] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of bis(2,2,2-trifluoroethyl)carbonate (FDEC) and FEC was used as the solvent.
[0142] [Example 4] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of methyl 3,3,3-trifluoropropionate (FMP) and FEC was used as the solvent.
[0143] [Comparative Example 1] A battery similar to that in Example 1 was fabricated, except that a mixed solvent of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TFETFPE) and FEC was used as the solvent.
[0144] [Example 5] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of TFEA and FEC in a volume ratio of 70:30 was used as the solvent.
[0145] [Example 6] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of TFEMC and FEC in a volume ratio of 70:30 was used as the solvent.
[0146] [Example 7] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of FDEC and FEC in a volume ratio of 70:30 was used as the solvent.
[0147] [Example 8] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of FMP and FEC in a volume ratio of 70:30 was used as the solvent.
[0148] Comparative Example 2 A battery was fabricated in the same manner as in Example 1, except that a mixed solvent of TFETFPE and FEC in a volume ratio of 70:30 was used as the solvent.
[0149] [Examples 9 to 18] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent having the composition shown in Table 2 was used as the solvent. Note that EMC in the table represents ethyl methyl carbonate.
[0150] [Examples 19 and 20] A battery was fabricated in the same manner as in Example 1, except that a mixed solvent having the composition shown in Table 3 was used as the solvent.
[0151] Comparative Example 3 A sulfur-microporous carbon composite was prepared in the same manner as in Example 1, except that microporous carbon (CNovel MH, manufactured by Toyo Tanso Co., Ltd.) was used instead of the mesoporous carbon used in Example 1. The physical properties of the microporous carbon were an average pore diameter of 5 nm and a micropore volume of 0.40 ccg. -1 , mesopore volume 0.25ccg -1 , specific surface area 1800m 2 g -1 It was. A battery was fabricated in the same manner as in Example 1, except that a sulfur-microporous carbon composite was used instead of the sulfur-mesoporous carbon composite in Example 1, and a mixed solvent of TFEMC and FEC in a volume ratio of 50:50 was used as the solvent.
[0152] Formulas (4) to (8) show the structures of TFEA, TFEMC, TFDEC, FMP, and TFETFPE, respectively. Formula (4) TIFF0007655726000003.tif4475 Formula (5) TIFF0007655726000004.tif3884 Formula (6) TIFF0007655726000005.tif3386 Formula (7) TIFF0007655726000006.tif3565 Formula (8) TIFF0007655726000007.tif4278
[0153] <Test Example 1> (Capacity retention at 10th cycle) For each of the batteries of Examples 1 to 8 and Comparative Examples 1 and 2, a charge-discharge cycle test was carried out under the following conditions. The battery was discharged at a constant current of 0.1 C to 1 V at 25°C. After discharge, it was charged at a constant current of 0.2 C to 3 V at 25°C. This discharge and charge process constitutes one cycle, and this cycle was repeated 12 times. After discharge and charge, a 10-minute rest period was provided at 25°C. Discharge, charge, and rest periods were all performed in a thermostatic chamber at 25°C. For the batteries after the charge-discharge cycle test, the ratio of the discharge capacity at the 12th cycle to the discharge capacity at the 3rd cycle was defined as the "capacity retention rate at the 10th cycle." The results of Examples 1 to 8, Comparative Examples 1 and 2 are shown in Table 1 below.
[0154] [Table 1]
[0155] Table 1 shows that the batteries of Examples 1, 4, 5, and 8, which contain the chain fluorinated carboxylic acid ester TFEA or FMP, exhibit higher capacity retention rates than the batteries of Comparative Examples 1 and 2, which do not contain the chain fluorinated carboxylic acid ester.
[0156] It is also clear that the batteries of Examples 2, 3, 6, and 7, which contain the chain fluorinated carbonate TFEMC or FDEC, exhibit high capacity retention, similar to the batteries of Examples 1, 4, 5, and 8, which contain the chain fluorinated carboxylic acid ester.
[0157] The examples using TFEA, TFEMC, or FMP showed higher capacity retention than the examples using FDEC in Examples 3 and 7. TFEA, TFEMC, or FMP have fewer bonded fluorine atoms than FDEC, which is thought to result in higher reduction resistance and higher capacity retention.
[0158] Comparing Examples 1 to 4 with Examples 5 to 8, it can be seen that a high capacity retention rate is exhibited even when the content of the chain fluorinated carboxylic acid ester or chain fluorinated carbonate in the nonaqueous electrolyte solution is changed.
[0159] The capacity retention was low in Comparative Examples 1 and 2, in which the nonaqueous electrolyte did not contain a chain fluorinated carbonate or a chain fluorinated carboxylic acid ester but contained 50 volume % or more of the chain fluorinated ether TFETFPE. This is thought to be because the reduction resistance of the chain fluorinated ether is lower than that of the chain fluorinated carbonate and the chain fluorinated carboxylic acid ester, and the chain fluorinated ether is reductively decomposed at the negative electrode.
[0160] From the above results, it can be said that a nonaqueous electrolyte secondary battery including a positive electrode containing a sulfur-mesoporous carbon composite can achieve a high capacity retention rate by using a nonaqueous electrolyte containing a chain fluorinated carbonate, a chain fluorinated carboxylic acid ester, or a combination thereof.
[0161] <Test Example 2> (Capacity retention at 100 cycles) For each of the batteries of Examples 9 to 18, the same test as the charge-discharge cycle test described above was carried out, except that the number of charge-discharge cycles was changed from 12 to 102 cycles. For the batteries after the charge-discharge cycle test, the ratio of the discharge capacity at the 102nd cycle to the discharge capacity at the 3rd cycle was defined as the "capacity retention at the 100th cycle." Table 2 shows the results of Examples 9 to 18.
[0162] [Table 2]
[0163] As is clear from Table 2, Examples 11 to 18, in which the nonaqueous electrolyte solution contained a chain fluorinated carbonate or a chain fluorinated carboxylic acid ester and a non-fluorinated solvent, EMC or EC, had a capacity retention rate of 100% at the 100th cycle, demonstrating that a nonaqueous electrolyte secondary battery with particularly excellent capacity retention rate after repeated charge and discharge can be realized.
[0164] <Test Example 3> (Initial discharge capacity, capacity retention at 10th cycle) The batteries of Examples 2, 19, and 20 were subjected to a charge-discharge test under the following conditions. The battery was discharged at a constant current of 0.1 C to 1 V at 25°C. After discharge, it was charged at a constant current of 0.1 C to 3 V at 25°C. This discharge and charge process constitutes one cycle, and this cycle was repeated 12 times. After discharge and charge, a 10-minute rest period was provided at 25°C. Discharge, charge, and rest periods were all performed in a thermostatic chamber at 25°C. For the batteries after the charge-discharge cycle test, the discharge capacity at the third cycle was defined as the "initial cycle discharge capacity." The ratio of the discharge capacity at the 12th cycle to the discharge capacity at the third cycle was defined as the "capacity retention at the 10th cycle." Table 3 shows the results of Examples 2, 19 and 20.
[0165] [Table 3]
[0166] As is clear from Table 3, the batteries of Examples 2, 19, and 20 all had excellent capacity retention rates. In particular, it was confirmed that the battery of Example 19 not only had a high capacity retention rate but also a high initial discharge capacity.
[0167] <Test Example 4> (Capacity retention at 10th cycle, capacity retention at 50th cycle) The batteries of Example 2 and Comparative Example 3 were subjected to a charge-discharge cycle test under the following conditions. The battery was discharged at a constant current of 0.1 C to 1 V at 25°C. After discharge, it was charged at a constant current of 0.2 C to 3 V at 25°C. This discharge and charge process constitutes one cycle, and this cycle was repeated 52 times. After discharge and charge, a 10-minute rest period was provided at 25°C. Discharge, charge, and rest periods were all performed in a thermostatic chamber at 25°C. For the batteries after the charge-discharge cycle test, the ratio of the discharge capacity at the 12th cycle to the discharge capacity at the 3rd cycle was defined as the "10th cycle capacity retention rate." The ratio of the discharge capacity at the 52nd cycle to the discharge capacity at the 3rd cycle was defined as the "50th cycle capacity retention rate." Table 4 shows the results of Example 2 and Comparative Example 3.
[0168] [Table 4]
[0169] Table 4 shows that the capacity retention can be increased by combining a positive electrode containing a sulfur-mesoporous carbon composite with a nonaqueous electrolyte containing a chain fluorinated carboxylic acid ester, while Table 4 shows that the capacity retention cannot be increased by combining a positive electrode containing a sulfur-microporous carbon composite with a nonaqueous electrolyte containing a chain fluorinated carboxylic acid ester. From the above, it can be understood that the effect of the present invention, which is to increase the capacity retention rate during repeated charge and discharge, is unique to the combination of a positive electrode containing a sulfur-mesoporous carbon composite and a nonaqueous electrolyte containing a chain fluorinated carbonate, a chain fluorinated carboxylic acid ester, or a combination thereof.
[0170] Although the present invention has been described in detail above, the above-described embodiments are merely examples, and the invention disclosed herein includes various modifications and alterations of the above-described specific examples. [Explanation of symbols]
[0171] 1 Non-aqueous electrolyte secondary battery 2 Electrode body 3 cases 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy storage unit 30 Energy storage device
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode and a non-aqueous electrolyte, The positive electrode includes a sulfur-mesoporous carbon composite in which a sulfur-based active material and mesoporous carbon are combined, the non-aqueous electrolyte contains a fluorinated solvent, the fluorinated solvent comprises a linear fluorinated carbonate, a linear fluorinated carboxylic acid ester, or a combination thereof; The mesoporous carbon is a porous carbon having a mesopore volume larger than a micropore volume, a nonaqueous electrolyte secondary battery in which the total content of the chain fluorinated carbonate and the chain fluorinated carboxylate in the nonaqueous electrolyte is 20% by volume or more;
2. 2. The nonaqueous electrolyte secondary battery of claim 1, wherein the fluorinated solvent comprises a cyclic fluorinated carbonate.
3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the nonaqueous electrolyte contains a non-fluorinated solvent.
4. 4. The nonaqueous electrolyte secondary battery according to claim 3, wherein the nonaqueous electrolyte contains the non-fluorinated solvent in an amount of from 1% by volume to 40% by volume.
5. 5. The non-aqueous electrolyte secondary battery according to claim 3, wherein the non-fluorinated solvent comprises a non-fluorinated organic compound containing a C=O double bond in the molecular structure.
6. the fluorinated solvent comprises a linear fluorinated ether; 6. The nonaqueous electrolyte secondary battery according to claim 1, wherein the fluorinated solvent contains the chain fluorinated ether in an amount of from 5% by volume to 15% by volume.
Citation Information
Patent Citations
Mesoporous carbon composite material and secondary battery using the same
JP2010095390A
Electrolyte solution for alkali metal-sulfur-based secondary battery, and alkali metal-sulfur-based secondary battery
WO2018163778A1